Contribution of income-related inequality and healthcare utilisation to survival in cancers of the lung, liver, stomach and colon. Issue 1 (19th October 2010) - Yim, Jun; Hwang, Seung-sik; Yoo, Keun-young; Kim, Chang-yup
Abstract : Objectives: To examine differences in the survival rates of cancer patients according to socioeconomic status, focusing on the role of the degree of healthcare utilisation by the patient. Methods: An observational follow-up study was done for 261 lung cancer, 259 liver cancer, 268 stomach cancer and 270 colon cancer patients, diagnosed during 1999–2002. Income status and healthcare utilisation were assessed with National Health Insurance (NHI) data; survival during 1999–2002 was identified by death certificate. HRs and 95% CI were derived from Cox proportional hazards regression. Results and Conclusions: The HRs for low income status are larger for colon cancer (2.37, 95% CI 1.17 to 4.80), followed by stomach (1.67, 95% CI 1.01 to 2.78), liver (1.57, 95% CI 1.03 to 2.39) and lung cancers (1.46, 95% CI 0.99 to 2.14). In the model including the variable of healthcare utilisation, colon and stomach cancers exhibited a lower HR in the moderate healthcare utilisation groups (0.40, 95% CI 0.21 to 0.76 in colon; 0.59, 95% CI 0.37 to 0.96 in stomach), whereas for liver cancer, the high utilisation group exhibited a higher hazard (1.72, 95% CI 1.07 to 2.75). A lower income status is independently related to a shorter survival time in cancer patients, especially in less fatal cancers. Healthcare utilisation independently affects the likelihood of survival from colon and stomach cancers, implying that a moderate degree of healthcare utilisation contributes to a longer survival time.